Celebrating March 8: a failed attempt at de-Sovietization?. Issue 1 (2nd January 2021) - Bula, Dace
ABSTRACT: Despite its international history of gender equality activism, Women's Day in the independent Baltic states in the twenty-first century resembles the way in which the day was celebrated in the Soviet past. The 'festival of gender' continues its existence, only slowly giving way to sporadic expressions of emancipatory ideas. It survives despite efforts in the three Baltic states to get rid of 'everything Soviet' during the process of regaining freedom including rituals and calendric practices. Proposing a polysemic reading of 8 March, this article interprets the contemporary meanings and practices of Women's Day in the post-socialist world.